Peacebuilding through Dialogue: Education, Human Transformation, and Conflict Resolution - Stearns, Peter N. (George Mason University, Fairfax, Virginia, 2018)
This volume examines the many dimensions of dialogue as a key driver of peaceful personal and social change. While most people agree on the value of dialogue, few delve into its meaning or consider its full range. The essays collected here consider dialogue in the context of teaching and learning, personal and interpersonal growth, and in conflict resolution and other situations of great change. Through these three themes, contributors from a wide variety of perspectives consider the different forms dialogue takes, the goals of the various forms, and which forms have been most successful or most challenging. With its expansive approach, the book makes an original contribution to peace studies, civic studies, education studies, organizational studies, conflict resolution studies, and dignity studies.
Identity, race, and classroom dialogue / Steven D. Cohen -- Listening and dialogue in educators' reflective practice / Bradley Siegel and William Gaudelli -- The presence and role of dialogue in Soka education / Jason Goulah -- Dialogue and agency: educating for peace and social change / Monisha Bajaj and Ion Vlad -- Compassion in dialogue / Bernice Lerner -- Bringing out the best in oneself and others: the role of dialogue in Daisaku Ikeda's peacebuilding practice / Olivier Urbain -- The WISE model and the role of self as observer in genuine dialogue / Meenakshi Chhabra -- Values, dissonance, and the creation of shared meaning / Gonzalo Obelleiro -- Dignity dialogues: an educational approach to healing and reconciling relationships in conflict / Donna Hicks -- Changing the conversation: emerging better dialogue practices seen through four lenses / Mark Farr -- Dialogue and mutual recognition: the practice of interreligious encounters / Andrea Bartoli and Charles Gardner -- Modes of peacemaking dialogue / Susan H. Allen -- Dialogue and demographic complexity / Ceasar L. McDowell
Includes bibliographical references and index.
Keywords: Peace-building; Interpersonal communication; Education -- Social aspects; Interpersonal communication; Education -- Social aspects; Peace-building